Upaya Peningkatan Hasil Belajar IPS Materi Konflik Dan Integrasi Dalam Kehidupan Sosial Melalui Metode Problem Based Learning Pada Siswa Kelas VIII E SMP Negeri 2 Srumbung Tahun Pelajaran 2019/2020 - Suindrati, Wiji (Faculty Of Education, 2022)
The fact that the learning outcome of Social study has’t given optimal one, always makes the problem faced by the teacher. There may be some problems for the students so that they can’t get the minimum grade stated by the school (KKM) Some of the problem which may be the case are; the lack of their participation in the lesson, the lack of their motivation in teaching learning process, especially in the discussion activities, the difficulty in making active interaction among them, and also the lack of their interest in character learning presented by their teacher. If this condition happens continuously and there is no concrete solution it may make any other problem for all the students. There are some ways to overcome this problem which can be taken by the teacher. One of them is making classroom action reasearh. One of the ways taken is to make reseach using Problem Based Learning method. The aim of the research is to improve learning outcomes of Social Study for students grade VIIIE of SMP Negeri 2 Srumbung of the academic year 2019/2020. The respondents of the research is 32 students. The data is taken from the research quantitative data from the outcome of observation of the teacher and the students as well. The quantitative data is in the form the outcome of the students’ assessment. In the first Cicle 1 there are 25 students get their minimum classical outcome 78, 13%. In the cicle 2 there is significan improvement in which there are 32 students get their minimum classical outcome 93,75%. Based on the result of the study it can be concluded that teaching learning Social study using Problem Based Leraning can improve the learning outcome for the students grade VIII E Of SMP N 2 Srumbung the academic year 2019/2020.